Lynx canadensis Kerr 1792 - W. Christopher Wozencraft (Smithsonian Institution Press, 1993)
Lynx canadensis Kerr, 1792. In Linnaeus, Anim. Kingdom, 1:157. TYPE LOCALITY: " Canada "; listed in Miller (1912b) as "Eastern Canada ". DISTRIBUTION: Taiga zone of North America, south to C Utah and SW Colorado, NE Nebraska, S Indiana, and West Virginia (USA). STATUS: CITES - Appendix II. SYNONYMS: mollipilosus Stone, 1900; subsolanus Bangs, 1897. COMMENTS: Considered distinct from L. lynx by Kurtén and Anderson (1980), Matyushkin (1979), Werdelin (1981), and Garcfa-Perea (1992). Weigel (1961) and Tumlison (1987) considered these taxa conspecific. Published as part of W. Christopher Wozencraft, 1993, Order Carnivora, pp. 279-348 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 293, DOI: 10.5281/zenodo.7359191